Highly conductive interconnected graphene foam based polymer composite. (December 2015) - Jun, Yun-Seok; Sy, Serubbabel; Ahn, Wook; Zarrin, Hadis; Rasen, Lathankan; Tjandra, Ricky; Amoli, Behnam Meschi; Zhao, Boxin; Chiu, Gordon; Yu, Aiping
Abstract: In this study, the impact of graphene sheet size on the electrical conductivity of interconnected graphene foam polymer composite is thoroughly investigated. Graphene oxide solution is produced from small flake graphite (SFG) (2–15 μm) and large flake graphite (LFG) (>100 μm), respectively. Each solution is used to produce three-dimensional GO foam, which is subsequently heat-treated to produce reduced graphene oxide (RGO) foam. The RGO foams are then infiltrated with poly(dimethylsiloxane) (PDMS) to produce graphene-PDMS (G-PDMS) composites. The in-plane electrical conductivity of the G-PDMS composite (0.4 wt%) from LFG reaches ∼3.2 S/m, which is more than two orders of magnitude greater than that of G-PDMS (1.9 wt%, 1.4 × 10 −2  S/m) from SFG. This value is also four orders of magnitude higher than that of the G-PDMS composite prepared from mechanical mixing of 4 wt% RGO powder made from SFG with PDMS (4.2 × 10 −5  S/m). The though-plane electrical conductivity followed the same trend for SFG and LFG. This reveals that the interconnected graphene foam supplies more efficient paths for electron transfer inside the polymer than conventional graphene powder and the use of large sized graphene sheets can significantly improve the electrical properties of G-PDMS.